An investigation of the evolutionary diversification of a recent radiation of dwarf chameleons (Bradypodion) from KwaZulu-Natal Province, South Africa - Da Silva, Jessica Marie (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.